2011
DOI: 10.1177/0013124511406916
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ Perception of Influence on Factors Affecting Student Achievement in Low- and High-Achieving Urban High Schools

Abstract: The purpose of the study was to compare and contrast influences principals have on staffing, curriculum issues, and discipline policies in high-and low-performing urban high schools. The data for the present study were drawn from the first year follow up of the Educational Longitudinal Survey of 2002-2004 (ELS: 02), administered by the National Center for Educational Statistics. Of the 14,000 school administrators surveyed, only high-and lowperforming urban high schools were included for this study. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…In this section, I put the findings in context of the extant literature and discuss the implications of the work. The finding that the relative level of influence over discipline policy varies significantly across stakeholders and levels of governance extends prior research that had only considered influence of a select few stakeholders or at select time points (Bloom & Owens, 2011;Ni, Yan, & Pounder, 2017;Shen, 1998;Ware & Kitsantas, 2011). The findings of this study suggest that perceived influence generally increases as one moves to more local levels of formal governance.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this section, I put the findings in context of the extant literature and discuss the implications of the work. The finding that the relative level of influence over discipline policy varies significantly across stakeholders and levels of governance extends prior research that had only considered influence of a select few stakeholders or at select time points (Bloom & Owens, 2011;Ni, Yan, & Pounder, 2017;Shen, 1998;Ware & Kitsantas, 2011). The findings of this study suggest that perceived influence generally increases as one moves to more local levels of formal governance.…”
Section: Discussionsupporting
confidence: 75%
“…For example, in a recent study, researchers found principals' reports of influence over discipline policy were greater than that of other stakeholders such as teachers, local school boards, state boards of education, or parent associations; however, the study was limited to data from a single year (Ni, Yan, & Pounder, 2017). In another study, Bloom & Owens (2011) found that in 2004 principals reported a higher level of influence over disciplinary policy as compared to influence over staffing, curriculum, or funding issues but that the level of influence did not vary systematically across urban and non-urban schools (Bloom & Owens, 2011). Other work confirms the finding that principals perceive school discipline to be one of the areas of their highest level of influence (Ni, Yan, & Pounder, 2017;Ware & Kitsantas, 2011) and suggests that throughout the late 1980s and early 1990s, there were increases in the perception of principal influence over discipline policy (Shen, 1998).…”
Section: Research On Influence Over School Discipline Policymentioning
confidence: 98%
“…The ELS is a nationally representative cohort study sponsored by the National Center for Educational Statistics (National Center for Educational Statistics, 2004). It includes multiple waves of student data; starting in the base year of 2002 when students were high school sophomores and concluding in 2012 when students were six years out of high school (see Bloom & Owens, 2013;Domina, 2009;Lowman & Elliott, 2010;& Museus & Vue, 2013 for additional analyses of the ELS data set).…”
Section: Data Source Sample and Proceduresmentioning
confidence: 99%
“…We coded articles as direct support when the study’s research questions and findings were central to what a leader must be able to know and do to influence building- or district-level outcomes and, therefore, directly related to the content of the standard(s). For instance, a study by Bloom and Owens (2013) investigated the different types of influences that principals in low-performing versus high-performing urban high schools had on policies regarding staffing, curriculum, and discipline. This study directly addressed the work of building-level leaders in terms of Standard 3 (organizational management).…”
Section: Methodsmentioning
confidence: 99%